Risiko Bencana Dalam Perspektif Ulama Dayah: Studi Kasus di Kabupaten Pidie Jaya - Sayed Yunus; Eka Sri Mulyani; Teuku Alvisyahrin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The role of Islamic dayah scholars in providing a perspective of disaster risk reduction to the people of Aceh has a very central position. The purpose of this study was to determine the perspectives of dayah scholars in Pidie Jaya in understanding the concepts and efforts of Disaster Risk Reduction (DRR) as well as its influence on community culture in responding to disaster issues. The sample in this study were 7 individuals from the Dayah Ulama group and 14 individuals from the community from various educational and professional backgrounds spread across Pidie Jaya Regency. Data collection was carried out by the process of field interviews and the collection of relevant documents from various sources. This study found Ulama in Pidie Jaya argued that disaster was a disaster from God in the form of reprimand to humanity and its prevention by patience and trying to avoid risks and pray to Allah. This study also found that the views of the Pidie Jaya community in responding to disaster risk were influenced by the opinions of ulama. The existence of scholars in the community as a reference shaft in religion and decision making in attitude. Scholars are very good at mediating Qur'anic knowledge using language that is easily understood by the public. This condition makes it strategic to make Dayah Ulema as catalysts for transforming disaster knowledge in the perspective of disaster risk reduction management to the community. As a center of social, it is very important to involve ulama in campaigning and carrying out disaster risk reduction actions undertaken by related parties.